Plantation life : corporate occupation in Indonesia's oil palm zone - Li, Tania, 1959-; Semedi, Pujo (Duke University Press, 2021)
"Tania Murray Li and Pujo Semedi examine the structure and governance of contemporary palm oil plantations in Indonesia, showing how massive forms of capitalist production and control over the palm oil industry replicate colonial-style relations that undermine citizenship."--